Short-Term Temporal Dynamics of VOC Emissions by Soil Systems in Different Biotopes - Monard, Cécile; Caudal, Jean-Pierre; Cluzeau, Daniel; Le Garrec, Jean-Luc; Hellequin, Eve; Hoeffner, Kevin; Humbert, Guillaume; Jung, Vincent; Le Lann, Cécile; Nicolai, Annegret (Frontiers in Environmental Science, 2021)
Volatile organic compounds (VOCs) are emitted by plants and microorganisms and have significant impacts on atmospheric chemistry. Soil systems are sources of VOCs driven by abiotic and biotic factors. We investigated the emissions of VOCs by soils and their plant cover from three contrasted biotopes: meadow, heathland and oak forest, during 24-hours in summer. We hypothesized that the spatial and temporal dynamics of VOC fluxes are reflected in soil properties, soil microbial communities, vegetation covers, and litter composition that differed in the three biotopesVOC fluxes were measured after direct on-field sampling at four sampling times (two at night and two at day) using a proton transfer reaction mass spectrometer, and results were linked to some climatic, edaphic and biotic parameters simultaneously monitored in each biotope. While differences in the composition of the soil bacterial communities, in the richness of the plant cover and in some soil physicochemical properties between the three biotopes were observed, the total VOC fluxes from the soil to the atmosphere did not present spatial patterns. However, differences in the mass composition of the VOC spectra were detected; for example, the soil from the forest that was covered with oak leaf litter had specific bacterial communities and emitted distinct VOC spectra than the two other biotopes. The total VOC fluxes responded to rainfall and were significantly driven by soil temperature. While we observed changes in the structure of soil bacterial communities between day and night in all biotopes using fingerprinting analysis, a diurnal dynamic of VOC fluxes was only observed in the forest biotope where the soil was protected from rainfall due to the canopy. This soil presented higher fluxes in day time up to 10.8 µg VOCs h-1 m-2 and lower fluxes in night time down to 3.8 µg VOCs h-1 m-2. Overall, the present study supplies data regarding VOC emissions by soils which are scare compared to plant sources. The results highlighted the complex interconnections existing between abiotic and biotic parameters that could directly or indirectly drive VOC emissions by soil systems.